Investigations on Empire series postage stamps of Ottomans (printed 1880-1890) by vibrational spectroscopic and energy dispersive X-ray fluorescence techniques - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2017)
In this study Empire series of stamps, the first postage stamps of Ottomans (printed in 1880-1890) after the Ottoman Empire became a member of Universal Postal Union, have been analyzed for the first time, non-destructively, using Fourier-transform infrared (FTIR), Raman and energy dispersive X-ray fluorescence (EDXRF) spectrometry methods Lead chromate, Prussian blue, vermillion, calcium carbonate, gypsum, cellulose, and oil were identified. The merging of data coming from vibrational spectroscopy and EDXRF techniques has allowed the characterization of the pigments used on the surface of each stamp and dispersed between the paper fibers. Additionally, the paper of the stamps was also analyzed. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: FTIR; Raman; EDXRF; Pigments; Postage stamps; Ottoman stamps; Ftir Spectroscopy; Raman Microscopy; Pigments; Inks; Identification; Spectrometry; Fibers